Pengaruh Literasi Membaca dan Pemanfaatan Perpustakaan Terhadap Prestasi Belajar Ekonomi Makro pada Mahasiswa Program Studi Pendidikan Ekonomi Universitas Sebelas Maret Surakarta - Fery Dwi Reginasari; Baedhowi Baedhowi; Salman Alfarisy Totalia (Department of Economics Education, Universitas Sebelas Maret, 2024)
The aims of this study is to determine and examine the effect of reading literacy and library utilization on the macro economics learning achievement of Economic Education students in Sebelas Maret University. This research is a quantitative research. The population of the research was the economic education students in Sebelas Maret University Surakarta batch 2015-2018 based on the weighting of macro economic credits. The sampling technique used was proportionate stratified random sampling. The samples were 171 respondents. Data collection techniques were interviews, questionnaires and documentation. The data analysis technique used multiple linear regression.The results of the research shows that (1) reading literacy has a positive and significant effect on macro economics learning achievement 6 credits and 3 credits (2) library utilization has a positive and significant effect on macro economics learning achievement 6 credits and 3 credits (3) literacy reading and library utilization have a positive and significant effect on macro economic learning achievement 6 credits and 3 credits. The value of R square macro economic 6 credits is 42.1%, the effective contribution of reading literacy is 26.4% and library utilization is 15.7%. and macro economic 3 credits is 38.8%, the effective contribution of reading literacy was 29.2% and library utilization is 9.6%, while the rest (100% -R Square) is effected by other factors not examined in this study. The effect of reading literacy and library utilization is bigger for students who take the macro economic 6 credits than students who take macro economic 3 credits in one semester. The meaning is the bigger the credit load borne by students influencing to the availability of their learning time, the higher the literacy reading and utilization of the library. So that can improve their learning achievement.